2022
DOI: 10.3390/land11020294
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Dairy Farms Transitioning to Environmentally Friendly Grazing Practices: The Case Study of Santa Catarina, Brazil

Abstract: The conflict between food production and environmental conservation demands alternative agriculture practices to maintain or increase food production, protect and restore critical ecosystem processes, and reduce dependence on non-renewable agricultural inputs. Deforestation in Brazil’s Atlantic Forest, for which agriculture has been a primary driver, already threatens the biome’s impressive biodiversity and the ecosystem services it helps sustain. Many small family farmers in Santa Catarina—located in the Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…We also measured positive impacts on ecosystem services. Farmers perceived that rotational grazing improved soil health and biodiversity [49,73], and farmers engaged in rotational grazing were significantly better informed about ecosystem services than conventional farmers [74,75]. We assessed the impacts of SPSnu on microclimate, pasture production, and pasture chemical composition, microclimate and biodiversity as compared to treeless pastures.…”
Section: Scientific Considerations: Designing Restorative Agroecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also measured positive impacts on ecosystem services. Farmers perceived that rotational grazing improved soil health and biodiversity [49,73], and farmers engaged in rotational grazing were significantly better informed about ecosystem services than conventional farmers [74,75]. We assessed the impacts of SPSnu on microclimate, pasture production, and pasture chemical composition, microclimate and biodiversity as compared to treeless pastures.…”
Section: Scientific Considerations: Designing Restorative Agroecosystemsmentioning
confidence: 99%
“…A separate study found that cows spend more than half their grazing time and nearly 2/3 of all time in the shade [66]. A separate study found that 97% of 60 farmers interviewed were aware that silvopastoral systems could reduce productivity losses to temperature extremes [74].…”
Section: Scientific Considerations: Designing Restorative Agroecosystemsmentioning
confidence: 99%
“…The efficiency assessments of family farm sustainability can use an indicator system that integrates economic, social and ecological values (Brasileiro-Assing et al, 2022;Damke et al, 2022;Savian et al, 2023). Economic value covered financial growth, resource utilization and organizational stability of family farms, expressed as the final income from all production and business activities, efficiency of utilizing production elements and resisting risks (Savickienė and Miceikienė, 2018;Micu et al, 2022).…”
Section: Background 21 Family Farm Sustainabilitymentioning
confidence: 99%
“…As respostas não foram afetadas por nenhuma das variáveis ligadas ao público amostral (P>0,05). Esta visão permite inferir que, na maioria das unidades produtivas, não há uma adesão plena ao método, e os produtores combinam princípios e práticas próprias do PRV com algumas alheias a este (BRASILEIRO-ASSING et al, 2022), o que pode afetar a estimativa de propriedades adotantes, antes apontada. Constata-se, pois, a existência do que se poderia considerar um "semi-PRV", algo como um modelo híbrido entre este e outros métodos.…”
Section: Adoção Do Prv Pelos Pecuaristasunclassified